2022
DOI: 10.1111/rec.13812
|View full text |Cite
|
Sign up to set email alerts
|

Introduced Spartina anglica modifies fish habitat in southern temperate succulent saltmarshes

Abstract: Vegetation changes in saltmarsh habitat can influence fish assemblages and abundance. In Tasmania, Australia, mid‐latitude succulent saltmarsh communities have been invaded by the introduced tall grass, Spartina anglica. Eradication efforts have been ongoing since the 1990s with purported benefits for fish access to intertidal foraging grounds, but a lack of knowledge of the impact of S. anglica on fish limits understanding of the benefits and effectiveness of native habitat restoration. Here, we investigate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…(P5): The encroachment of the invasive grass species, Spartina anglica , into temperate saltmarsh and its effect on local fish communities was studied in an eradication experiment conducted by Harrison‐Day et al (2023), Tasmania, Australia. The results revealed that the eradication of invasive grass had a strong positive effect on fish species richness, diversity, and abundance.…”
Section: Field‐based Studies (P1–p15)mentioning
confidence: 99%
“…(P5): The encroachment of the invasive grass species, Spartina anglica , into temperate saltmarsh and its effect on local fish communities was studied in an eradication experiment conducted by Harrison‐Day et al (2023), Tasmania, Australia. The results revealed that the eradication of invasive grass had a strong positive effect on fish species richness, diversity, and abundance.…”
Section: Field‐based Studies (P1–p15)mentioning
confidence: 99%